Role Of Diffusion Weighted Magnetic Resonance Imaging In Brain Pathologies (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background: Diffusion weighted imaging (DWI) has a wide range of applications in  the evaluation of brain pathologies. This study was conducted to correlate Diffusion  weighted MR imaging features of brain pathologies with other MRI sequences, to  evaluate the role of DWI in brain pathologies. A prospective, observational and  cross section study was performed of 100 patients in 6-month period. Patient with  clinical suspicion of stroke, CNS infections, head injury, demyelination and tumor  were included. All MRI studies were done on Siemens magneto essenza 1.5 T MRI.  Age wise distribution, complaints, intra and extra axial location of tumor, presence  and absence of restricted diffusion and findings of various sequences of MRI were  studied.  Methods: The present study was conducted in the Department of Radiology at AMC  MET Medical college and LG hospital. Participants after understanding the study  protocol and procedure were asked to give their written consent for the study. Results: in our study maximum cases were observed from 5th to 6th decades. 91  cases were intra-axial, 9 were extra-axial. 52% cases of stroke comprised of arterial  infarct (39%), venous infarct (4%), HIE (3%), PRES (4%) and parenchyma  haemorrhage (2%). 17% of cases were tumours which included glioma, metastases,  GBM and hemangiopericytoma. 5% case of cavernous haemangioma and 5% cases  of arachnoid cysts. 15% case of brain infections were included. All acute and  subacute arterial infarcts and all venous infarcts showed restriction on diffusion  weighted images and chronic cases did not show restriction. High grade gliomas,  astrocytomas, and metastases showed diffusion restriction.
Keywords: DWI; Intracranial brain pathology; MRI (Magnetic resonance imaging); T2W (T2 weighted); FLAIR; ADC